Bugs in the Blood: The Rise of Blood Parasites in Raptors - Arent, Lori (Wildlife Rehabilitation Bulletin, 2008)
Two blood parasite diseases, avian malaria and babesiosis, are increasing in prevalence in raptor species. Avian malaria, the more commonly reported of the two, is documented as deadly; the severity of babesiosis is currently unknown. Routine evaluation of blood smears is critical to diagnosing these diseases so that appropriate treatment can be initiated and unexpected mortalities prevented.